Modernizace pavlačového bytového domu, Petrská 4, Praha, stavebně technologická příprava stavby - Hamerníková, Veronika (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Cílem této diplomové práce je řešení stavebně technologické přípravy modernizace pavlačového bytového domu v Praze 1 v ulici Petrská. Hlavním předmětem řešení diplomové práce jsou bourací práce ve stávajícím objektu a nový strop nad 3. NP. Součástí této práce je stavebně technologická zpráva, technická zpráva k zařízení staveniště, technologické předpisy bouracích prací a stropní konstrukce nad 3. NP – ve dvou variantách provedení, porovnání dvou technologií provedení stropní konstrukce nad 3. NP, kontrolní a zkušební plány, návrh strojní sestavy, dopravní vztahy, plán bezpečnosti a ochrany zdraví při práci, environmentální plán, harmonogram prací a časový a finanční plán modernizace.

Diploma thesis focuses on solving of the technological preparation of building modernization of gallery residential building in Prague 1 at Petrska street. The main goal of the thesis is a demolition of the existing building and construction of a new ceiling above the third floor. The paper includes the construction and technological report, technical report for concruction site equipment, technological regulations of demolition works and the ceiling structure above the third floor – there are two design variants of the ceiling structure icluded. The variants contend a comparation of two technologies version of ceiling structure above the third floor. Thesis also includes the inspection and test plans, design of machine arrangement, transport relations, safety and health protect plan, environmental plan, work and time schedule and financial calculation of building modernization
Modernization gallery residential building, Petrská street, Praha, civil technological project
Keywords: Modernizace; technologický předpis; strojní sestava; zařízení staveniště; harmonogram; bourací práce; stropní konstrukce; stavebně technologická zpráva; dopravní vztahy; kontrolní a zkušební plán; ochrana životního prostředí; hluk; prašnost.; Modernization; technologic regulation; machine arrangement; construction site equipment; schedule; demolition works; ceiling construction; condtruction and technology report; transport relations; inspection and test plan; environmental protection; noise; dust.